Healthy through Magic: Health Solutions in Mantra Kidung Jawa - Onok Yayang Pamungkas; Sahid Teguh Widodo; Suyitno Suyitno; Suwardi Endraswara (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
This research seeks to uncover and provide critical arguments of magical meaning in Mantra Kidung Jawa (after this referred to as MKJ). The focus of the investigation is the author's form and motive to create the spell. Various text models are considered strategies for magical purposes. This qualitative method of hermeneutics and content analysis was used as a research guideline. The object of the study is a collection of MKJ texts in Serat Kidungan's book published by the publisher Maha-Dewa, Ngajogjakarta Hadiningrat, 1957. This research data is in the form of text that implicitly contains magical meanings. Research shows that the magical power of mantras is still believed to influence Javanese life in the past. There is a correlation of 'interaction' between literature and mantras. The content of MKJ text is nostalgic, which repeatedly conveys and reminds of mythological figures, which are often mysterious. MKJ has relationships with various religions, both Hindu and Islamic. This proves that there is always the possibility of creativity when traditions side by side with religion that lasts for a long period. Kebenaran ini merupakan sinyal untuk yaitu sinyal untuk yaitu yaitu Y kedua, kekuatan teks mantra terletak pada keyakinan atas energi supranatural yang berasal dari imaji magis alam, tokoh mitologi, dan Bahasa Indonesia. Beri beri kerangka penelitian ini adalah bahwa MKJ bisa ber pada studi transdisipliner di daerah kesehatan di balik teks mistik. Warisan leluhur Jawa melalui mantra bisa bisa menjadi kata-kata untuk kehidupan yang luar, termasuk krisis kesehatan global akibat Covid-19.